KLASSIFIKASI BAHAN ORGANIK TANAH BUKIT PINANG-PINANG KAWASAN HUTAN HUJAN TROPIK GUNUNG GADUT PADANG - Yulnafatmawita Yulnafatmawita; Asmar Asmar; Mimien Harianti; Suci Betrianingrum (Jurnal Solum, 2009)
A research about soil organic matter (SOM) classification based on the density was conducted for soil in Bukik Pinang-Pinang region.  The objective of this research was to identify whether the SOM in Pinang-Pinang area, having very high annual rainfall, was mostly particulate or had been associated with mineral particles.  Soils were sampled at three different land use, forest, bush, and mixed wood land on 0-10, 10-20, and 20-30 cm soil depth.  Soil organic matter was classified into 2 classes, < 1.0 g cm-3 and ≥ 1.0 g cm-3 by using pure aquadest.  Total and fractionated SOM samples were analyzed by using Walkley and Black method in soil laboratory, Agriclculture College, Andalas University.  The result showed that, among the three land use surveyed, mixed wood land use gave the highest SOM, then followed by bush land.  Soil OM content in forest ecosystem was much lower than the other two land use for the whole depth.  Based on the density, SOM particulate was higher on the soil surface and decrease by depth in each land use.  Among the ecosystem, SOM under forest was less associated with soil particles than that under bush and mixed wood land. Key Words:  SOM-light fraction, SOM-heavy fraction, land use